Hemorrhagic Transformation of Cerebral Infarction – Possible Mechanisms - Hamann, Gerhard F.; del Zoppo, Gregory J.; von Kummer, Rüdiger (Thrombosis and Haemostasis, 1999)
To analyse the risk/benefit of cerebral thrombolysis the role of hemorrhagic transformation, either as clinically silent hemorrhagic infarction or disastreous parenchymal hemorrhage, is crucial. Thrombolysis in acute ischemic stroke increases the risk of severe, life-threatening hemorrhagic complications by up to 10 times compared to controls. In this paper, previous proposed concepts for the development of intracerebral hemorrhage and hemorrhagic transformation are presented. The role of the cerebral microvasculature will be emphasized. In experimental focal cerebral ischemia a significant loss of basal lamina components of the cerebral microvessels has been demonstrated. This loss in vessel wall integrity is associated with the development of petechial hemorrhage. The mechanisms for this microvascular damage may include plasmin-generated laminin degradation, matrix metalloproteinases activation, transmigration of leukocytes through the vessel wall, and other processes. We propose that attenuation of the microvascular integrity loss with subsequent reduction in hemorrhage is theoretically possible 1) by an improvement in the definition of an individual time window of therapy (by means of imaging techniques), 2) by a biochemical quantification of the basal lamina damage to avoid dangerous interventions, and 3) by pharmacological strategies to protect the basal lamina during thrombolysis.
Keywords: Hemorrhagic transformation; intracerebral hemorrhage; cerebral infarction; thrombolysis; microvasculature